THE SOCIAL DIMENSION OF THE ASSET QUALITY REVIEW IN THE EUROPEAN UNION - Lukovic, Vesna (Bank Indonesia, 2024)
During the financial crisis that started in 2008, banks in the European Union (EU) needed state aid to stay afloat. After years of bailing out failing banks with public money, which led to high public debt levels across the EU, the European Commission introduced the bail-in approach. This approach required stress tests and asset quality reviews (AQR) to identify capital shortfalls in the various banking systems. The idea was to review the quality of banks’ assets, including the collateral valuations and the adequacy of assets and other collateral provisions. This study focuses on the case of Slovenia, the first EU member state that applied a bail-in approach even before it became a legally binding law at the EU level. The Slovenian bail-in led to the cancellation of all subordinated obligations (shares or bonds) held by thousands of investors, mainly private individuals. The information asymmetry and data confidentiality argument together with the applied assumptions in AQR and stress tests have raised questions about the reliability and credibility of the national and EU authorities in this respect. This paper focuses on the social/human dimension of this case by presenting the current situation through the lens of the temporal dimension of former investors’ plight in their legal attempts to challenge those extraordinary measures. The paper revolves around data confidentiality and other issues that have contributed to the fact that this situation remains unresolved, more than ten years after the nationalisation measures. The finding of this analysis is that former investors have had no legal means to effectively challenge nationalisation measures because the authorities in Slovenia have failed to provide an appropriate tool that would be effective and available in practice.